Sustainable Development of Indonesia’s Land Border Areas; Overview from an Economic Perspective - Dian Anggraeny Rahim; Dominicus Savio Priyarsono; Ernan Rustiadi; Yusman Syaukat (Muhammadiyah University Press, 2023)
The development of land border areas is continuously inevitable, so the government annually rolls out programs and policies. The sustainability of this development is expected to make the border area a center of economic growth, have a multiplier effect on the surrounding area, reduce poverty and backwash the economy, attract investment, and improve the country's income. In comparison, eliminates problems in the land border area, such as low indicators of development performance and regional isolation. This research was conducted in provinces with land border areas, namely West Kalimantan, East Kalimantan, North Kalimantan, East Nusa Tenggara, and Papua. Observations were made from 2015 – 2020 using secondary data sourced from the Central Bureau of Statistic. The research method used Principal Component Analysis to reduce thirteen to six variables of government programs supporting development performance in border areas. The reduced factors then used as variables in the Data Regression Panel to find out what programs affecting gross domestic product, poverty, and human development index in Indonesia's land border areas. The fifth variables are investment, health, agriculture, road infrastructure and markets and transportation. All variables have a significant effect on poverty and human development index, but not gross domestic product. This result shows a government economic strategy for developing sustainable land border areas.